Desert giant : the world of the saguaro cactus - Bash, Barbara (Boston : Little, Brown, Boston : Little, Brown, 1989)
Documents the life cycle and ecosystem of the giant saguaro cactus and the desert animals it helps to support.
Keywords: Saguaro -- Juvenile literature; Saguaro -- Juvenile literature. -- Juvenile literature; Desert ecology -- Juvenile literature; Saguaro; Cactus; Desert ecology; Ecology